Product hacking as a systematic intervention: towards new strategies and platforms in design education - (:unkn) unknown (SPRINGER, 2021)
This paper is mainly about how product hacking can be categorized and implemented in a systematic way in design education. The theoretical or analytical part of the project is based on a study in which a great number of hacking projects are reviewed and categorized found in popular DIY platforms. The implementation or synthesis part of the research is a design project held in an industrial design department with freshman design students based on the categorization of function proposed, which are namely; enhance, change and add function. In this project students are required to make three kinds of interventions on functions of existing products, also share their projects in the selected platform (www.instructables.com), so that other people can find, criticize, develop, or apply it by using the instructions given. Sharing in platforms like these creates a connection between the analytical and synthetic phases of the paper, and also makes it different from other classical projects confined to a closed studio atmosphere. This paper also seeks for the possibility of fresh perspectives on issues like sustainability, ready-made and open source design by engaging students in an intervention-based design process where they look for formulating their designs in a methodological way. One other aspect of the project was the idea that it has the potential to create an advantage or value for the time and context it was given, that is when the COVID-19 has started to influence our lives deeply.
Keywords: Design education; Product hacking; Intervention; DIY platforms; COVID-19; Sustainability; FAILURE